(untitled) (One Health & Risk Management, 2023)
Introduction. Adenocarcinomas are the most common lung tumors and are often diagnosed in advanced stages when the tumor has a polyclonal form with a wide variety of genetic alterations and activated mutational processes. Comprehensive analysis of mutational status from FFPE tissue samples in such patients can provide a therapeutic perspective and contribute considerably to clinical decisions thereby increasing the overall survival rate. Material and methods. 22 genes were analyzed for mutations and 4 genes for fusion transcripts using two Ion AmpliSeq panels. DNA was isolated from paraffin-embedded tissue sections while RNA analysis was performed using two types of samples: paraffin blocks and fresh tumor tissue. Key variant detection and data analysis was performed using next platforms: Ion Reporter, ONCOMINE, R language. Results. The study of 30 tumor samples allowed the detection of 147 mutations and 4 fusions in 19 genes, and the therapeutically actionable variants were associated with different drugs clinically approved or in the phase of clinical trials. The most genetic variants were identified in the TP53, EGFR and NOTCH1 genes with a prevalence of over 50% in the TP53 gene, while all 4 detected fusions (one fusion per sample) represent the association of the ALK gene with other partners: EML4(13)-ALK(20) – present in 2 samples; EML4(6)-ALK(20); and an ALK fusion with an unknown partner gene. Conclusions. Analyzing the mutational status of tumor samples from patients with lung adenocarcinoma it has been ascertained the therapeutic utility of gene panel sequencing covering point mutations, INDELs and SNVs, as well as gene fusions, using FFPE tissue as primary material. This is valid for both targeted monotherapies and combined therapies.